2023
DOI: 10.1126/scitranslmed.add2712
|View full text |Cite
|
Sign up to set email alerts
|

Lactate oxidase nanocapsules boost T cell immunity and efficacy of cancer immunotherapy

Zheng Cao,
Duo Xu,
Jeffrey Harding
et al.

Abstract: Cancer immunotherapy has reshaped the landscape of cancer treatment. However, its efficacy is still limited by tumor immunosuppression associated with the excessive production of lactate by cancer cells. Although extensive efforts have been made to reduce lactate concentrations through inhibition of lactate dehydrogenase, such inhibitors disrupt the metabolism of healthy cells, causing severe nonspecific toxicity. We report herein a nanocapsule enzyme therapeutic based on lactate oxidase, which reduces lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The acid environment of tumors plays an important role in tumor formation and development, can promote tumor cell proliferation, invasion, and migration, and can create iTME to reduce the immune surveillance of tumor cells by host cells. 114 The low pH in TME inhibits Tcell-mediated immune responses by downregulating mTORC1 expression 115 and interferes with the antitumor activity of NK cells, 116 while reducing the expression of M1 macrophage related factors iNOS, CCL2, and IL-6 in tumor tissues, increasing the expression of M2-type macrophage related factors and promoting the polarization of tumor-associated macrophages to M2. 117 The studies described above showed that the design of nanoplatforms for lactate regulation could alleviate tumor immunosuppression and improve the efficacy of antitumor therapy.…”
Section: Regulation Of Lactate In Tmementioning
confidence: 99%
See 1 more Smart Citation
“…The acid environment of tumors plays an important role in tumor formation and development, can promote tumor cell proliferation, invasion, and migration, and can create iTME to reduce the immune surveillance of tumor cells by host cells. 114 The low pH in TME inhibits Tcell-mediated immune responses by downregulating mTORC1 expression 115 and interferes with the antitumor activity of NK cells, 116 while reducing the expression of M1 macrophage related factors iNOS, CCL2, and IL-6 in tumor tissues, increasing the expression of M2-type macrophage related factors and promoting the polarization of tumor-associated macrophages to M2. 117 The studies described above showed that the design of nanoplatforms for lactate regulation could alleviate tumor immunosuppression and improve the efficacy of antitumor therapy.…”
Section: Regulation Of Lactate In Tmementioning
confidence: 99%
“…Tumor cells have a more active glucose uptake ability and can digest glucose through the glycolysis pathway and produce large amounts of lactic acid. The acid environment of tumors plays an important role in tumor formation and development, can promote tumor cell proliferation, invasion, and migration, and can create iTME to reduce the immune surveillance of tumor cells by host cells . The low pH in TME inhibits T-cell-mediated immune responses by downregulating mTORC1 expression and interferes with the antitumor activity of NK cells, while reducing the expression of M1 macrophage related factors iNOS, CCL2, and IL-6 in tumor tissues, increasing the expression of M2-type macrophage related factors and promoting the polarization of tumor-associated macrophages to M2 .…”
Section: Application Of Tumor Microenvironment Modulated Nanoplatform...mentioning
confidence: 99%
“…In two different mouse models, treatment of these nanocapsules augmented the effects of immune-checkpoint blockade therapy without causing toxicity to other organs. 16 Interestingly, some bacteria can consume lactate in hypoxia. Wang et al prepared a bioreactor composed of Shewanella oneidensis MR-1 (SO) and DOX-loaded MIL-101 (Fe-base MOF).…”
Section: Metabolism-targeted Nanomedicine For Cancer Therapymentioning
confidence: 99%
“…In contrast, nanostructure-based formulations can not only effectively protect them from direct contact with active substances, but also improve their PK profiles in vivo , eventually leading to an enhanced therapeutic efficacy. 16,17 (3) Multifunctionality. Metabolic therapy usually requires combinatory treatments to achieve a high therapeutic index.…”
Section: Introductionmentioning
confidence: 99%
“…First, we established a balb/c mice model of triple-negative breast cancer that is difficult to be treated by chemotherapy in the clinic (Figure a) . Nanomedicine has unique biological effects, such as targeted effects on tumor site with loose vessels. Subsequently, in vivo biodistribution of NPt IV @siXkr8&Cy7 was further studied, and the change of fluorescence at the tumor site was detected via an in vivo imaging system following a single dose of intravenous administration. As shown in Figure b, the fluorescence from NPt IV @siXkr8&Cy7 appeared at the tumor site 4 h after injection and reached its maximum intensity at 24 h. Obvious fluorescence still remained at the tumor site 72 h after injection.…”
Section: Introductionmentioning
confidence: 99%